Use of lignocellulolytic microbial consortium and pH amendment on composting efficacy of rice straw - Kausar, Hossain; Ismail, Mohd Razi; Mohd Saud, Halimi; Othman, Radziah; Habib, Sheikh Hasna (Taylor & Francis, 2013)
The present study was conducted at the Composting Unit, Universiti Putra Malaysia to determine the physico-chemical changes, microbial dynamics, and enzyme activities during microbial composting of rice straw at different pH conditions. Different treatments comprising of composting substrates (A), substrates with microbial consortium (B), substrates, microbial consortium, and acetic acid (C), substrates, microbial consortium, and sodium hydroxide (D) were used to enhance the composting process of rice straw. In inoculated treatments, the temperature increased rapidly to higher than 50°C by day 5 and remained above 40°C up to day 17, while in the control the temperature increased slowly and peaked (46°C) at day 9 and remained above 40°C until day 23. The results showed that biodegradation was at its maximum in microbial-infused treatments within 14–21 days as indicated by profiles of pH, reduction of C/N ratio, lignocellulolytic (lignin peroxidase, endoglucanase, and exoglucanase) enzyme activities, and lignocellulose bioconversion. After day 21, the C/N ratio of microbial-infused treatment without any pH adjustment (B) was reduced to 17.5 from an initial value of 29.2 suggesting that there were no additive effects of pH adjustment during the microbial composting of rice straw.